GE_GERICHTE P/24863/2021 vom 20. Dezember 2022 - GE Cour de justice (2022)
ORDONNANCE DE CLASSEMENT;RECEL;PRÉVENU;FRAIS DE LA PROCÉDURE;DÉPENS;IMPUTATION;INDEMNITÉ(EN GÉNÉRAL);FAUTE;PRINCIPE DE LA BONNE FOI | CPP.319; CPP.426; CC.3.al2; CP.160